Introduction: Druze Studies Journal, Issue 1, 2024 - Zeedan, Rami (Druze Studies Journal, 2024)
The inaugural issue of the Druze Studies Journal (DSJ) represents a pivotal moment for advancing interdisciplinary research on the Druze. Despite longstanding scholarly interest, studies on the Druze have often been fragmented across disciplines and lacked a dedicated platform. DSJ seeks to fill this gap by fostering a global and collaborative scholarly community. This open-access journal highlights diverse perspectives on Druze history, religion, politics, identity, and linguistics, featuring contributions from leading academics and emerging researchers. The first issue covers a wide range of topics, including Druze sociopolitical dynamics, linguistic practices, and religious beliefs, while also providing forums on seminal works in Druze Studies. Launched during a 2023 symposium, DSJ aims to overcome challenges faced by non-native English speakers and promote accessible, high-quality scholarship. Future initiatives include a 2025 interdisciplinary conference, further solidifying DSJ's commitment to advancing knowledge and fostering critical engagement within the field of Druze Studies.